Менеджмент: внутрішні та зовнішні змінні організації - Брінь, Павло Володимирович; Прохоренко, Олена Вікторівна (Національний технічний університет "Харківський політехнічний інститут", 2024)
Management is the process of planning, organizing, leading, and controlling resources—such as people, finances, and materials—to achieve specific goals and objectives efficiently and effectively. It is essential in organizations to coordinate efforts, streamline operations, and ensure that tasks are completed in a manner that maximizes productivity while minimizing costs. Management is important because it ensures that an organization's resources—whether human, financial, or material—are used efficiently and effectively to achieve its goals. Here are key reasons why management is crucial: Goal Achievement: Management helps set clear objectives and aligns the organization's efforts towards achieving them. Without proper management, goals can become unclear, leading to inefficiencies. Optimal Resource Utilization: Through effective planning and organization, management ensures resources like time, money, and manpower are used in the best possible way, reducing waste and increasing productivity. Adaptation to Change: Good management enables organizations to be flexible and adapt to market changes, technology advancements, and other external factors. Managers monitor the environment and adjust strategies to stay competitive. Problem Solving: Managers identify potential issues before they escalate, offering solutions and keeping operations smooth. They help teams navigate challenges and overcome obstacles. Employee Motivation: Leadership within management motivates and guides employees, fostering a productive work environment. Clear direction and support boost employee morale and performance. Innovation and Growth: Management encourages innovation by setting an environment where creativity is valued, enabling the organization to grow and evolve over time. In the lecture notes you will find the main milestones of management science and description of internal and external variables of the organization.
Management: internal and external variables of the organization
Keywords: lecture notes; history of management; approaches to management; internal variables of the organization; external environment of the organization; introduction to management